Diagnosis and management of liver disease - Kirsch, Ralph E; Robson, Simon; Trey, Charles (Chapman & Hall Medical, 1995)
The publication focuses on diagnosis and therapy of various liver diseases. Intended for professional public.
Keywords: hepatologie; Disease Management; nemoci jater; management, organizace a řízení zdravotnictví; Liver Diseases; management nemoci